2017
DOI: 10.1016/j.agrformet.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Climate controls over the net carbon uptake period and amplitude of net ecosystem production in temperate and boreal ecosystems

Abstract: The seasonal and interannual variability of the terrestrial carbon cycle is regulated by the interactions of climate and ecosystem function. However, the key factors and processes determining the interannual variability of net ecosystem productivity (NEP) in different biomes are far from clear. Here, we quantified yearly anomalies of seasonal and annual NEP, net carbon uptake period (CUP), and the maximum daily NEP (NEP max) in response to climatic variables in 24 deciduous broadleaf forest (DBF), evergreen fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 83 publications
4
57
0
1
Order By: Relevance
“…The IAVs of the land C sink at global and regional scales are in agreement with observations at ecosystem scales. For example, the observed NEE by the eddy covariance towers changed from 74 to 930 g C/m 2 /year at the site US‐Blo (Blodgett Forest in the Sierra Mountains of California) and from −158 to 240 g C/m 2 /year at the site Be‐Bra (De Inslag Forest in Brasschaat, Belgium) during the period from 1997 to 2007 (Fu, Stoy, et al, ). Across the 24 sites that have > 8 years of continuous measurement, the SD of NEE on average accounts for 50% of annual NEE (Figure b).…”
Section: Observed Phenomena Of Interannual Variation In Land Carbon Smentioning
confidence: 99%
“…The IAVs of the land C sink at global and regional scales are in agreement with observations at ecosystem scales. For example, the observed NEE by the eddy covariance towers changed from 74 to 930 g C/m 2 /year at the site US‐Blo (Blodgett Forest in the Sierra Mountains of California) and from −158 to 240 g C/m 2 /year at the site Be‐Bra (De Inslag Forest in Brasschaat, Belgium) during the period from 1997 to 2007 (Fu, Stoy, et al, ). Across the 24 sites that have > 8 years of continuous measurement, the SD of NEE on average accounts for 50% of annual NEE (Figure b).…”
Section: Observed Phenomena Of Interannual Variation In Land Carbon Smentioning
confidence: 99%
“…Fu et al. () showed that a 1‐d advance in spring phenology was associated with a 1.6 g C/m 2 increase in NEP in spring (March–May), but no impact on annual NEP in grasslands. However, in contrast to previous studies, we found that an advance in spring phenology only affected GEP and NEP during EGS (20–50 d after SOS) rather than the whole spring season at most sites.…”
Section: Discussionmentioning
confidence: 99%
“…, Fu et al. ), while the differences in the relationships between the changes in spring phenology and the dynamics of GEP, NEP, and ER were not fully revealed. (3) The date of green‐up derived from remote sensing or EC CO 2 flux time‐series data based on different thresholds was treated as a static phenological event (Richardson et al.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations